Peran Evaluasi dalam Meningkatkan Standar Pendidikan di Era Digital - Yosep Sudarso; Nadap Rafi Ghungnga; Eki Yanto Neonisa; Yerliani Boymau; Hemi Damnosel Bara Pa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Educational evaluation plays a crucial role in improving educational standards, especially in the digital era characterized by advancements in information technology. This study aims to identify how effective evaluation can enhance the quality of education through the use of digital tools. The method used is qualitative descriptive with a literature review approach, where data is collected through analysis and description of information from various sources, including books and journal articles. The results indicate that digital-based evaluations, such as the use of online platforms and assessment applications, improve the accuracy and efficiency in collecting student learning data. Additionally, formative evaluations conducted continuously provide constructive feedback, enhance student motivation, and allow for curriculum adjustments that are more responsive to learning needs. Challenges faced, such as evaluator subjectivity and technological access gaps, were also identified but can be addressed through training and capacity building for educators and students.